PREPARATION OF ACCOUNTING RECORDING SYSTEM AT KID'S KINGDOM STORE - Budi Chandra; Michelle Willestania (ConCEPt - Conference on Community Engagement Project, 2022)
Every business requires an efficient and accurate accounting record system so that business owners can more easily find out the condition of business through financial reports that have been prepared using the recording system. This community service is carried out to support MSMEs who have difficulty in compiling an accounting record system. The MSMEs chosen for this service is the Kid's Kingdom Store, which is located at Nagoya Hill Mall, Batam. Kid's Kingdom Store has been operating for 10 years but does not have an efficient and accurate accounting record system. Kid's Kingdom Store uses a manual recording system and only records daily income. The research methods used in this service are observation, interviews, and documentation. This service is expected to help MSME owners to make financial reports such as income statements, statements of financial position, purchase reports, sales reports, and cash receipts reports. Recommendation for the future project is researcher can make a manual book for owner so that owner can recall how to use the system easily. Thank you for giving researcher to do this community service. Hope this activity can be helpful for community.